2022
DOI: 10.1080/16549716.2022.2067395
|View full text |Cite
|
Sign up to set email alerts
|

Prioritising and mapping barriers to achieve equitable surgical care in South Africa: a multi-disciplinary stakeholder workshop

Abstract: Background Surgical healthcare in South Africa is inequitable with a considerable lack of resources in the public health sector. Identifying barriers to care and creating research priorities to mitigate these barriers can contribute to strategic interventions to improve equitable access to quality surgical care. Objective To use the Four Delays Framework to map barriers to surgical care and identify priorities to achieve equitable and timely access to quality surgical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…This work describing the creation and evolution of a single surgical unit adds to the large body of the literature on medical care and surgery in LMIC environments in general and Haiti specifically, which includes discussions of facility funding, barriers to effective care and shortcomings of current volunteer programs, comments on how to improve access to care, surveys of multiple facilities, and a combined description of previous cases at St Luke’s and a similar institution in Honduras [ 2 , 5 , 8 , 10 , 12 , 19 , 21 , 23 , 26–38 , 45 , 46 ]. In the existing literature, there are similar examples of scaling up of surgical care in rural Haiti, which has been described by the Partners in Health and the Zanmi Lasante (PIH/ZL) organisations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This work describing the creation and evolution of a single surgical unit adds to the large body of the literature on medical care and surgery in LMIC environments in general and Haiti specifically, which includes discussions of facility funding, barriers to effective care and shortcomings of current volunteer programs, comments on how to improve access to care, surveys of multiple facilities, and a combined description of previous cases at St Luke’s and a similar institution in Honduras [ 2 , 5 , 8 , 10 , 12 , 19 , 21 , 23 , 26–38 , 45 , 46 ]. In the existing literature, there are similar examples of scaling up of surgical care in rural Haiti, which has been described by the Partners in Health and the Zanmi Lasante (PIH/ZL) organisations.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing surgical care in resource-limited nations continues to represent a difficult and multifaceted effort combining acquisition and maintenance of medical infrastructure and equipment, training and recruiting local and foreign physicians, and sustaining long-term high-quality performance [ 47–49 ]. We have demonstrated that a three-phase plan, detailed earlier, can address these simultaneous challenges, and here we briefly discuss our plan in the context of the so-called delay framework (or delay model) to global health, which owes its origin to a maternal mortality program in sub-Saharan Africa [ 8–12 ]. Our three-phase plan, which led to a sustainable surgical centre in Haiti, addresses the main barriers to surgical care recently identified with the four delay framework, apparent by considering the description herein compared with barrier prioritisation in Table 1 [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations